PI3K signaling: a molecular pathway associated with acute hypophagic response during inflammatory challenges - Borges, Beatriz C (Mol Cell Endocrinol, 2016)
Energy balance has in the hypothalamus a central component of integration of food intake and energy expenditure. An accumulating body of evidence indicates that energy homeostasis is largely affected by inflammatory challenges. Severe undernutrition caused by exacerbated inflammatory response may lead to cachexia. On the other hand, prolonged low-grade inflammation such as that observed in obesity and metabolic syndrome, raises the risk for the development of diabetes and heart diseases. Changes in circulating insulin and cytokines such as leptin, interleukins and tumor necrosis factor, as well as changes in their action in the hypothalamus drive the inhibition of food consumption during inflammation. The molecular pathways associated with these responses have only started to be unraveled. One potential candidate is the PI3K signaling, an important player in distinct hypothalamic neurons that control food intake. This study presents an overview of the current knowledge about PI3K role on cytokines and insulin signaling in the hypothalamic regulation of feeding during inflammation.